2018
DOI: 10.1590/1809-2950/17243825012018
|View full text |Cite
|
Sign up to set email alerts
|

Controle postural de mulheres com dismenorreia primária em dois momentos do ciclo menstrual

Abstract: RESUMO A dismenorreia primária (DP) é uma dor pélvica ou abdominal inferior relacionada à menstruação, associada a pontos dolorosos miofasciais, cuja presença é capaz de alterar a percepção somatossensorial e a ativação muscular, o que pode interferir no controle postural. O objetivo deste estudo foi verificar a influência da DP no controle postural estático de mulheres em dois momentos do ciclo menstrual, com e sem dor. Foram avaliadas 19 universitárias (22,4±3,0 anos) com DP por meio da escala visual analógi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(42 reference statements)
0
1
1
3
Order By: Relevance
“…It should be emphasized that no studies were found that evaluated the PF pressure threshold in women with and without PD. In the present study, in relation to the values found in the non-menstrual phase, it was observed that the PF pain threshold values were lower than those of the studies evaluating the abdomen and anteroposterior iliac spines 16 . In addition, no reference values were found for women in this age group for comparison.…”
Section: Discussioncontrasting
confidence: 45%
“…It should be emphasized that no studies were found that evaluated the PF pressure threshold in women with and without PD. In the present study, in relation to the values found in the non-menstrual phase, it was observed that the PF pain threshold values were lower than those of the studies evaluating the abdomen and anteroposterior iliac spines 16 . In addition, no reference values were found for women in this age group for comparison.…”
Section: Discussioncontrasting
confidence: 45%
“…We will sum the results of the ventral measurement of the right and left sides to calculate the mean of the results. The calculation will be the same for dorsal [ 26 ]. It is important to note that algometry demonstrates validity and internal consistency among evaluators ranging from 0.84 to 0.99.…”
Section: Methodsmentioning
confidence: 99%
“…Área Temática: Fisioterapia Musculoesquelética E-mail do autor para correspondência: liliancostaa_@hotmail.com RESUMO Introdução: A dismenorreia é definida como um episódio doloroso que ocorre durante o período menstrual, especialmente, na região abdominal inferior. Quando há ausência de doença pélvica concomitante, esta é denominada dismenorreia primária (Stallbaum et al, 2018). As opções de tratamento para essa patologia incluem ações integradas e múltiplas entre uma equipe multiprofissional (Prazeres et al 2018).…”
Section: Fortalecimento Muscular Sobre Equilíbrio E Marcha Em Pacientes Com Esclerose Múltipla: Revisão Bibliográficaunclassified